Genome-Wide Association Study for Grain Micronutrient Concentrations in Wheat Advanced Lines Derived From Wild Emmer - Liu, Jia; Huang, Lin; Li, Tingxuan; Liu, Yaxi; Yan, Zehong; Tang, Guan; Zheng, Youliang; Liu, Dengcai; Wu, Bihua (Frontiers in Plant Science, 2021)
Wheat is one of the important staple crops as the resources of both foods and micronutrient for most people of the world. However, the lower concentration or deficiencies of especially iron (Fe), zinc (Zn) and other essential micronutrients in staple food, causing micronutrient malnutrition or hidden hungry, have affected a large proportion of the world population's health. Biofortification is an effective way to increase the micronutrient concentration of wheat. Wild emmer (Triticum dicoccoides, AABB, 2n=4x=28) is the ancestor species of durum wheat and common wheat with high concentration of Fe, Zn and Mn, which is an important genetic resource for wheat micronutrient improvement. In this study, we report a genome-wide association study (GWAS) using 13116 DArT-seq markers to characterize grain Fe, Zn and Mn (manganese) concentration (GFeC, GZnC, GMnC) in 161 wheat lines derived from wild emmer. Using both general linear model and mixed linear model, we identified 14 high-confidence significant marker-trait associations (MTAs) that were associated with GFeC, GZnC, and GMnC, of which 9 MTAs were novel. 6 MTAs distributed on chromosomes 3B, 4A, 4B, 5A and 7B were significantly associated with GFeC. 3 MTAs on chromosomes 1A and 2A were significantly associated with GZnC and 5 MTAs on 1B were significantly associated with GMnC. These MTAs have no negative effects on thousand kernel weight (TKW) and should be useful for simultaneous improvement of micronutrient concentrations and TKW in wheat breeding. Additionally, we identified genotypes containing favorable MTAs and recommended 61 top genotypes with a higher concentration of beneficial grain micronutrients (Fe,Zn, and Mn), which could be utilized in the breeding program for the genetic biofortification. Searches of public databases revealed 38 putative candidate/flanking genes related to micronutrient concentrations. The putative proteins of interest were grouped in four main categories: enzymes, metal transport-related proteins, MYB transcription factor and unknown proteins. The MTAs and associated candidate genes provide essential information for wheat biofortification breeding by marker-assisted selection (MAS).